Crewel : a novel / 1. - Albin, Gennifer (Albin, Gennifer. Crewel world, 2012)
Gifted with the unusual ability to embroider the very fabric of life, sixteen-year-old Adelice is summoned by Manipulation Services to become a Spinster, a move that will separate her from her beloved family and home forever.